Analisis Komunikasi Siswa Kelas 6 SD Dalam Mengimplementasikan Muatan Lokal Materi Unggah-Ungguh Basa Jawa (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
The existence of Javanese language learning in the era of modern technology among the younger generation is starting to decline. Considering the Javanese language is a learning that does not only emphasize language and culture learning but as an effort to preserve culture, one of which is uploading the Javanese language. The purpose of this research is to analyze the understanding and implementation of the Javanese language variety upload material when communicating with other people. With this research, it is hoped that the obstacles experienced during the Javanese language learning process can be overcome. This research uses a qualitative method with a case study approach involving a Javanese language teacher and 50 students from two elementary schools. Sources of data from interviews, questionnaires, and written exams for students. The data were analyzed using the analytical model of Milles and Huberman starting from the collection, reduction, and presentation of data, and drawing conclusions. The results showed that the factors causing the decline in the existence of the Javanese language among elementary school students were due to the lack of precise teaching methods for subject teachers, the social environment of children, and the absence of proper habituation of Javanese language children in the family. Based on the results of the questionnaire sheet, it was found that students had difficulty in distinguishing various Javanese languages ​​such as ngoko, krama, and krama inggil. Students tend to generalize the use of Javanese for parents, teachers, and friends when communicating.